AI-Powered Learning: Shaping the Future of Academic Writing in EFL Education in Indonesia - Hapsari, Elsa Widya; Sudarman, Sudarman (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2025)
This study investigates the use of artificial intelligence (AI) in English as a Foreign Language (EFL) academic writing teaching, with an emphasis on problems and perceptions among Indonesian teachers and students. To analyze prevalent challenges connected to AI use in education, data were collected using a qualitative descriptive approach from teacher comments, classroom observations, and relevant literature. The findings highlight five important themes: low digital literacy, unequal access to infrastructure, student overreliance on AI technologies, a lack of pedagogical training, and varied teacher attitudes towards AI in the classroom. Despite these challenges, many Indonesian EFL teachers recognise AI's potential to assist personalised learning, streamline feedback processes (especially via conferencing), and improve instructional methods. This study advances our understanding of AI's educational impact in Indonesian EFL environments, emphasising the importance of focused professional development and equal access to technology.